The Toll Route to Structural Brain Plasticity - Li, Guiyi; Hidalgo, Alicia (Frontiers in Physiology, 2021)
The human brain can change throughout life, as we learn, adapt and age. Balance between structural brain plasticity and homeostasis characterises the healthy brain, and breakdown of this balance accompanies brain tumours, psychiatric disorders and neurodegenerative diseases. However, the link between circuit modifications, brain function and behaviour remains unclear. Importantly, the underlying molecular mechanisms are starting to be uncovered. The fruit-fly Drosophila is a very powerful model organism to discover molecular mechanisms and test them in vivo. There is abundant evidence that the Drosophila brain is plastic, and here we travel from the pioneering discoveries to recent findings and progress on molecular mechanisms. We pause on the recent discovery that in the Drosophila central nervous system, Toll receptors – which bind neurotrophin ligands - regulate structural plasticity during development and in the adult brain. Through their topographic distribution across distinct brain modules and their ability to switch between alternative signalling outcomes, Tolls can enable the brain to translate experience into structural change. Intriguing similarities between Toll and mammalian Toll-Like Receptor function could reveal further involvement in structural plasticity, degeneration and disease in the human brain.